(untitled) (Medicine Today, 2019)
Introduction: Diabetic neuropathy is one of the early complications of diabetes mellitus patients which is very difficult to face in the daily living activities. The purpose of the present study was to see the demographic characteristics of diabetic neuropathy patients. Metarials & Methods: This descriptive type of cross-sectional study was conducted in the Department of Neurology including Neuropathy Clinic and in collaboration with department of Endocrinology at Banghabandhu Sheikh Mujib Medical University, Dhaka from January 2012 to December 2013 for a period of two (2) years. Adult diabetic patients presented with neuropathic pain with symmetrical involvement of distal limbs from indoor and outpatient department of Neurology including Neuropathy clinic as well as indoor and outpatient department of Endocrinology, BSMMU were enrolled in the study population. Data was collected by face to face interview. Information was collected by taking medical history and clinical examinations and subsequent laboratory investigations. Results: A total number of 102 cases were recruited for this study who were clinically diagnosed as painful diabetic polyneuropathy. Female was predominant than male 55(53.9%) cases and 47(46.1%) cases respectively. The male and female ratio was 1:1.2. Majority were in the age group of more than 55 years which was 55(53.9%) cases. The mean age with SD of the study population was 52.79±9.42 years. Among 102 patients type II DM was predominate than type I patients which were 95(92.2%) cases and 8(7.8%) cases respectively. The mean duration of DM with SD was 6.51±3.6 years. However the mean duration of neuropathic pain was 1.68±1.155 years. Conclusion: In conclusion majority of the diabetic neuropathy patients are female suffering from type II DM in the middle age. Medicine Today 2019 Vol.31(1): 27-30